Type B coalho cheese with the addition of aqueous coriander extract (Research, Society and Development, 2020)
Coalho cheese produced with cow's milk is a typical product of Brazil, being considered a heritage of the Northeast region, where it originated. This adds a source of income for its producers and traders, moving the economy of several cities. Thus, this work aims to evaluate the action of the aqueous extract of coriander leaves added to rennet cheese against the microorganisms Salmonella spp. and Staphylococcus aureus as well as to analyze the sensory quality of this product after the addition of the extract and its influence on some physical parameters - chemical. It can be observed that in the sensory evaluation, coriander promoted small changes in the evaluated parameters, as well as in the physical-chemical aspects, but they were not statistically significant. The microbiological evaluation showed a reduction in the content of S. aureus for the cheese containing the extract. We concluded that more studies are needed to evaluate the microbial reduction in the sample containing the aqueous extract of coriander and that the acceptability of the cheese was positive.